Papel do estresse oxidativo na cardiotoxicidade aguda e crônica induzida por doxorrubicina - Segredo, Manuella Pacifico de Freitas [UNESP] (2017)
The mechanism of doxorubicin-induced cardiotoxicity remains controversial. Wistar rats (n=66) received doxorubicin (DOX) injections intraperitoneally and were randomly assigned to two experimental protocols: 1) rats (n=16 ) were killed before and 24 h after a single dose of DOX (4 mg/Kg-body-wt) to determine the DOX acute effect; 2) rats (n=60) received 4 injections of DOX (4 mg/Kg-bodywt/ week) and were killed before the first injection (M0) and 1 week after each injection (M1, M2, M3, M4) to determine the chronological effect. Cardiac total antioxidant performance (TAP), DNA damage and morphology analyses were done at each time point. Body weight, clinical signs and necropsia changes were also registered. DOX single dose was associated with increased cardiac disarrangement, necrosis and DNA damage [strand breaks (SBs) and oxidized pyrimidines], and decreased TAP. Single dose of DOX was not associated with changes in body weight, clinical signs and necropsy.The chronological study showed an effect of a cumulative dose on body weight (R - 0.99, P 0.011), necrosis (R 1.00, P 0.004), TAP (R 0.95, P 0.049), and DNA SBs (R - 0.95, P 0.049). DNA SBs damage was negatively associated with TAP (R - 0.98, P 0.018) and necrosis (R - 0.97, P 0.027). The necropsy showed abnormalities (heart softening, ascites, pleural effusion, adhesion between organs and hydronephrosis) from M3. Our results suggest that oxidative damage is associated with acute cardiotoxicity induced by a single DOX only. Increased resistance to the oxidative stress is plausible for the multiple dose of DOX.